IPFS Based Secure and Decentralized Web Architecture A Systematic Review - Dhimas Tribuana; Apriani Sijabat; Titih Nursugiharti; Rizky Charles Wijaya (Pandawan, 2026)
The rapid development of digital technology has driven a transition from Web 2.0 to Web 3.0, where decentralization, user autonomy, and data security have become fundamental priorities. This transition introduces critical challenges in distributed systems, peer-to-peer networking, and security engineering, particularly concerning fault tolerance, data integrity, and resilience against centralized failures. Traditional centralized web architectures often suffer from single points of failure, making them vulnerable to cyberattacks and censorship. This study investigates the InterPlanetary File System (IPFS) as a content-addressed, peer-to-peer distributed storage architecture that enhances decentralized web infrastructures by enabling immutable data validation, node redundancy, and improved resistance to system-level attacks. This study adopts a Systematic Literature Review (SLR) approach to examine the application of IPFS in developing secure and decentralized websites within the Web 3.0 ecosystem. Following PRISMA-guided procedures, recent peer-reviewed studies are systematically analyzed to identify architectural patterns, security mechanisms, and system-level challenges associated with decentralized web hosting. The findings are synthesized to assess the implications of IPFS for data integrity, system resilience, and fault tolerance in distributed environments. These results lead to the conclusion that integrating IPFS into website development represents a strategic step toward creating a more transparent, resilient, and decentralized web ecosystem aligned with the core principles of Web 3.0.